Pentingnya Peranan Guru Mengatasi Bullying di Sekolah Dalam Mewujudkan Sekolah Ramah - Dorlan Naibaho; Elsa Yulinarda Yahya Nainggolan (Pusat Riset dan Inovasi Nasional, 2023)
The aim of this research is to describe the role of teachers in overcoming bullying as an effort to create a friendly school and the perceived obstacles. The purpose of this research is to determine the duties and roles of teachers in dealing with bullying to create a friendly school. The research method uses a qualitative approach with qualitative descriptive methods. The data collection technique used in this research is library research. The results of this research show the role of teachers in dealing with bullying, namely planning anti-bullying actions, finding the root of the problem of bullying, giving punishment, forming study groups, advising students who bully, providing guidance and counseling, services, offering gifts or rewards, offering